Renewable energies, public policies, national solid waste policy and taxes - Catapan, Anderson (2020)
This editorial features articles from the first issue of the ninth volume of the Brazilian Journal of Planning and Development – Revista Brasileira de Planejamento e Desenvolvimento (RBPD). This issue has contributed to the planning and development, as in previous and usual numbers of this journal, by teachers from Brazil.